Rice NICOTIANAMINE SYNTHASE 2 expression improves dietary iron and zinc levels in wheat - Singh, Simrat Pal (Theor Appl Genet, 2016)
KEY MESSAGE: Iron and zinc deficiencies negatively impact human health worldwide. We developed wheat lines that meet or exceed recommended dietary target levels for iron and zinc in the grains. These lines represent useful germplasm for breeding new wheat varieties that can reduce iron and zinc deficiency-associated health burdens in the affected populations. ABSTRACT: Micronutrient deficiencies, including iron and zinc deficiencies, have negative impacts on human health globally. Iron-deficiency; anemia affects nearly two billion people worldwide and is the cause of reduced cognitive development, fatigue and overall low productivity. Similarly, zinc deficiency causes stunted growth, decreased immunity and increased risk of respiratory infections. Biofortification of staple crops is a sustainable and effective approach to reduce the burden of health problems associated with micronutrient deficiencies. Here, we developed wheat lines expressing rice NICOTIANAMINE SYNTHASE 2 (OsNAS2) and bean FERRITIN (PvFERRITIN) as single genes as well as in combination. NAS catalyzes the biosynthesis of nicotianamine (NA), which is a precursor of the iron chelator deoxymugeneic acid (DMA) required for long distance iron translocation. FERRITIN is important for iron storage in plants because it can store up to 4500 iron ions. We obtained significant increases of iron and zinc content in wheat grains of plants expressing either OsNAS2 or PvFERRTIN, or both genes. In particular, wheat lines expressing OsNAS2 greatly surpass the HarvestPlus recommended target level of 30 % dietary estimated average requirement (EAR) for iron, and 40 % of EAR for zinc, with lines containing 93.1 µg/g of iron and 140.6 µg/g of zinc in the grains. These wheat lines with dietary significant levels of iron and zinc represent useful germplasm for breeding new wheat varieties that can reduce micronutrient deficiencies in affected populations. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00122-016-2808-x) contains supplementary material, which is available to authorized users.